Information sharing and channel encroachment in biomass supply chains. - Xin Wu; Peng Liu; Jin Li; Jing Gao; Guangyin Xu (PLoS ONE)
To guarantee the sustainable development of the biomass raw material supply chain, researchers are increasingly focusing on the issue of information asymmetry between biomass power plants and upstream supply chain members. This paper investigates the optimal information sharing strategy for a biomass power plant where farmers choose whether to encroach on the biomass feedstock supply. Using a game theory model, we analyze eight different information sharing scenarios, and the results show that when the encroachment occurs in supply chain channels, information sharing can significantly increase the profits of the entire supply chain. In this case, the power plant should share its demand information with all upstream players to promote the overall benefit of the supply chain. In contrast, when the power plant shares its information only with the middleman, it can maximize its profits, which, however, may not be conducive to the long-term stability of the supply chain. Furthermore, surprisingly, in the absence of channel encroachment, the power plant sharing information with upstream members may harm their profits. This suggests that power plants may need to consider the scope of information sharing more carefully when the farmers choose not to encroach. Finally, we also examine the impact of channel competition intensity on information sharing strategies, and find that when channel competition intensity is low, transparent demand information helps the power plant maximize expected returns. However, in a highly competitive market environment, the power plant should carefully handle information sharing with farmers to avoid damaging their profits.